Stabilization of soft clay soil by the reinforcement of single bottom ash silica fume (BASF) column - Ng, Jun Shen; Muzamir, Hasan; Tan, Kah Yee (Semnan University Press, 2024)
This research examined the utilization of bottom ash mixed with silica fume in the ground improvement technique by constructing columns beneath the soft clay. Utilizing the bottom ash was an effective method and easily available in the market and the application of silica fume in the study improved the result through its pozzolanic characteristics. The vibro-replacement method was implemented during the bottom ash column installation process. The properties of the materials involved in the research were examined by suitable geotechnical tests complying with relevant standards. The important parameter, shear strength was accessed by conducting the Unconfined Compression Test (UCT). In this study, a total of seven (7) batches of soil samples were involved comprising the control sample. From each batch, it had five (5) soil samples which included the 14 mm and 20 mm diameter of column with the height of 60 mm, 80 mm, and 100 mm. From the results of shear strength improvement, the 14 mm diameter column with height penetrating ratios of 0.6, 0.8, and 1.0 were showing 58.97%, 88.56%, and 69.81% respectively. The next column design which had the 20 mm diameter with the height penetrating ratio of 0.8, recorded the highest improvement of 38.73%, followed by 1.0 and 0.6 which resulted in 32.81% and 19.19% respectively. The use of correlation technique had streamlined the complexity of the independent variables and verified the reliability of the results through the R2 value. In summary, the improvement in shear strength was significantly influenced by the column design.